‘Educating Indonesia’ and the Minister Who’s Making It Happen - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Energy and optimism were highlights of the recent speech given by Indonesia’s Trade Minister Gita Wirjawan during the SMU Presidential Distinguished Lecturer Series. While the optimism may be rooted deeply in the potential of Indonesia’s current demographic — more than 30 percent of its population is aged between 19 and 24, and more than 50 percent is under 29, making it one of the youngest productive populations in the world — its economic success story is fact, reflected in its G-20 membership, where it is the second fastest growing economy.Yet much remains to be done to unleash the full potential of this segment, says Wirjawan.